The Science and Knowledge in the ‘Invisible City’ - Erica Mariosa Carneiro; Maria Clara Rodriguez Sosa; Ana de Medeiros Arnt (Educação & Realidade, 2023)
This article analyzes the erasures of popular culture in favor of scientific knowledge, from the series Invisible City. Therefore, the series is analyzed with conceptual tools from Michel Foucault and Ailton Krenak. The series premiered in 2020 on a streaming platform, and is about Brazilian folk entities living in a community in Rio de Janeiro. The invisibility refers both to the nonexistence of the characters in the rational world and to the context of peripheral experience. The counterpoints between popular and scientific knowledge are constructed in the narrative, bringing elements from Brazilian histories without simultaneously pretending to be faithful to their cultural productions.